A development of indicators for the sustainability assessment of the Mexican power system planning - Hernandez-Hurtado, Ulises; Martin-del-Campo, Cecilia (International Journal of Sustainable Energy Planning and Management, 2021)
Countries with emerging economies face a significant challenge when developing strategies to move towards a low emission energy system and keep their economies growing. The power System plays a crucial role in these strategies and by the correct measurement of its sustainability is possible to identify which alternative improves sustainability the most. This article proposes indicators for the evaluation and assessment of the sustainability of Mexican Power System planning scenarios put forward by two government administrations with a study horizon to 2030. The scenarios are characterized by the program of additions and retirements of generating capacity along the period of 2019 to 2030, and eventually, optimal dispatch was obtained to accomplish the hourly demand. Sustainability indicators were developed and calculated to evaluate the energy security, energy equity and environmental sustainability dimensions. Subsequently the indicators were fed to the Position Vector of Minimum Regret Analysis as multicriteria decision analysis. By analysing the results, it is highlighted that the expansion of power grid capacity, as well as the hourly availability of hydro plants improve the sustainability of the Mexican Power System. The comparison between both scenarios’ performance, based on the Energy Trilemma, indicates that the current government’s planning is slightly more sustainable.